Evaluating the long-term strength of GGBFS-blended cement across various water-to-binder and superplasticizer ratios under heating/cooling cycles - Bashdar Omer; Najmadeen Mohammed Saeed; Mahmood Hunar Dheyaaldin; Ahmed Salah Jamal; Rawaz Kurda (PLoS ONE, 2025)
The investigation is to understand the combined effects of ground granulated blast furnace slag (GGBFS) content, superplasticizer (SP) dosages, and water-to-binder (w/b) ratios on the fresh and harden properties, as well as long-term durability under thermal cycles. This study aims to address these gaps by examining the influence of varying GGBFS replacement levels, SP dosage, and w/b ratios on blended mortar’s fresh properties, mechanical strength, thermal performance, water absorption, and microstructure. The experimental method included testing for flowability, fresh density, and compressive strength over 56 and 90 days and 30% for 365 days and evaluating the microstructure through microscopy. The result showed that increasing GGBFS content improved both flowability and fresh density. Additionally, thermal cycling led to a significant increase in compressive strength with an average strength gain of 22% at 56 days, 40.9% at 90 days, and 30% at 365 days. The microstructure, which demonstrates a lot of calcium silicate hydrate (C-S-H) crystals and is relatively denser after 365 days, results in high strength. In conclusion, incorporating GGBFS in cement composites reduces CO2 emissions, improves performance, and enhances durability, especially under thermal conditions, making it a viable solution for providing high-performance concrete. This finding has significant implications for reducing the environmental footprint and life cycle in construction.